'Principles governing the construction of the Silimba, a xylophone type found among the Lozi of Zambia', by Atta Annan Mensah.'Ghanaian xylophone studies', by Mitchel Strumpf.'Oral notation of some West and Central African time-line patterns', by Gerhard Kubik. 'Fieldwork in African music', by John Blacking - Tracey, Andrew (International Library of African Music, 1973)
pages: 99
Keywords: Musical instruments; Lozi (African people); Xylophone; African Music; Ghana; Zambia; Silimba (Instrument); Xylophone (Instrument)